Market leader - Rogers, John (Pearson Education, 2006)
This gives extra practice in the areas of grammar and vocabulary, together with a complete syllabus in business writing *Students work with text models and useful language, then do a writing task to consolidate the learning *Provides regular self-study pronunciation work with audio CDs or cassettes and exercises